2008
DOI: 10.1021/cm703095z
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature Solvothermal Synthesis of Phosphorus-Rich Transition-Metal Phosphides

Abstract: Solvothermal reactions between a metal chloride (CoCl2, NiCl2, and CuCl2) and dissolved yellow phosphorus in superheated toluene (275 °C) yield nano- or submicrometer sized particles of amorphous metal phosphides that, upon modest annealing (350–500 °C), crystallize to phosphorus-rich metal phosphides CoP3, NiP2, and CuP2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
49
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 39 publications
1
49
0
Order By: Relevance
“…[5,6] In recent years, considerable efforts have been devoted to the synthesis of nanostructured transition-metal phosphides. For instance, Co 2 P nanoparticles supported on silica were synthesized by thermal treatment of [Co 2 (CO) 6 [7] Nanostructured Co 2 P, Ni 2 P, CoP, FeP, and MnP were prepared by hydrothermal and solvothermal methods using yellow phosphorus (P 4 ) [8,9] and by a desilylation strategy using tris(trimethylsilyl)phosphine (PA C H T U N G T R E N N U N G (SiMe 3 ) 3 ). [10] Moreover, Fe 2 P, FeP, Co 2 P, CoP, Ni 2 P, and MnP nanocrystals were also made by solution-phase methods using trioctylphosphine (TOP), metal phosphine complexes, long-chain alkylphosphonic acids, and single-source molecular precursors containing elemental metal and phosphorus.…”
Section: Introductionmentioning
confidence: 99%
“…[5,6] In recent years, considerable efforts have been devoted to the synthesis of nanostructured transition-metal phosphides. For instance, Co 2 P nanoparticles supported on silica were synthesized by thermal treatment of [Co 2 (CO) 6 [7] Nanostructured Co 2 P, Ni 2 P, CoP, FeP, and MnP were prepared by hydrothermal and solvothermal methods using yellow phosphorus (P 4 ) [8,9] and by a desilylation strategy using tris(trimethylsilyl)phosphine (PA C H T U N G T R E N N U N G (SiMe 3 ) 3 ). [10] Moreover, Fe 2 P, FeP, Co 2 P, CoP, Ni 2 P, and MnP nanocrystals were also made by solution-phase methods using trioctylphosphine (TOP), metal phosphine complexes, long-chain alkylphosphonic acids, and single-source molecular precursors containing elemental metal and phosphorus.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16] Barry et al reported an anhydrous solvothermal route to prepare phosphorous-rich transition metal phosphides without using an excess of phosphorous. 17 Perera et al used P(SiMe 3 3 to react with iron(III) acetylacetonate and manganese(III) acetylacetonate to prepare FeP and MnP nanoparticles. 18 Liu's group and Brock's group noted that trioctylphosphine (TOP) can be used as a phosphorous source in replace of very reactive P(SiMe 3 3 to form metal phosphides.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Cobaltrelated materials, including metallic cobalt, [2] cobalt oxide, [3] cobalt alloy, [4] and cobalt phosphide, [5] have been used in magnetic materials, aerospace engineering, and energy storage. With the development of modern nanoelectronic technology and the increasing demand for nanostructured materials, [6] the preparation of nanostructured inorganic cobaltcontaining materials has become a crucial technological challenge.…”
mentioning
confidence: 99%